Under-attending free antenatal care is associated with adverse pregnancy outcomes - Heinonen Seppo; Heiskanen Nonna; Raatikainen Kaisa (BMC, 2007)
Abstract Background Most pertinent studies of inadequate antenatal care concentrate on the risk profile of women booking late or not booking at all to antenatal care. The objective of this study was to assess the outcome of pregnancies when free and easily accessible antenatal care has been either totally lacking or low in number of visits. Methods This is a hospital register based cohort study of pregnancies treated in Kuopio University Hospital, Finland, in 1989 - 2001. Pregnancy outcomes of women having low numbers (1-5) of antenatal care visits (n = 207) and no antenatal care visits (n = 270) were compared with women having 6-18 antenatal visits (n = 23137). Main outcome measures were: Low birth weight, fetal death, neonatal death. Adverse pregnancy outcomes were controlled for confounding factors (adjusted odds ratios, OR: s) in multiple logistic regression models. Results Of the analyzed pregnant population, 1.0% had no antenatal care visits and 0.77% had 1-5 visits. Under- or non-attendance associated with social and health behavioral risk factors: unmarried status, lower educational level, young maternal age, smoking and alcohol use. Chorio-amnionitis or placental abruptions were more common complications of pregnancies of women avoiding antenatal care, and pregnancy outcome was impaired. After logistic regression analyses, controlling for confounding, there were significantly more low birth weight infants in under- and non-attenders (OR:s with 95% CI:s: 9.18 (6.65-12.68) and 5.46 (3.90-7.65), respectively) more fetal deaths (OR:s 12.05 (5.95-24.40) and 5.19 (2.04-13.22), respectively) and more neonatal deaths (OR:s 10.03 (3.85-26.13) and 8.66 (3.59-20.86), respectively). Conclusion Even when birth takes place in hospital, non- or under-attendance at antenatal care carries a substantially elevated risk of severe adverse pregnancy outcome. Underlying adverse health behavior and possible abuse indicate close surveillance of the newborn.